Three new species of the subfamily Microgastrinae (Hymenoptera: Braconidae) from Vietnam - Long, Khuat Dang (Academia Journal of Biology, 2014)
1. Apanteles allofulvigaster Long K, sp. n. (figs 1-6) Material: Holotype, 1♀Mic.668: VN, Hanoi, Gialam, fruit orchard, MT 20o59’N 105o55’E, 22.VI- 08.VII.2001, K. D. Long. Holotype: ♀, length of body 2.8 mm, of fore wing 3.1 mm, ovipositor 1.8 mm. Head (figs 1, 2). Antenna as long as body; third antennal segment 0.95 times fourth segment; penultimate segment equal to apical segment; head in frontal view not converging below; width of face 1.3 times height of face and clypeus combined; height of eyes 2.1 times its width; antennal sockets slightly higher than middle level of eyes; tentorial pits small, distance between from pits 3.2 times distance from pits to eye margin; head in dorsal view transverse with temple roundly narrowed (fig. 2), its width 1.7 times its height; ocelli in low triangle; POL 0.8 times OOL and 2.0 times Od. Face rather flat, polished with sparse and sharp punctures; vetex and temple with sparse punctures. Mesosoma: width of mesonotum width 1.3 times width of head, mesoscutum with dense discrete punctation; scutellar sulcus narrow and with carinae; scutellum polished with sparse sharp punctures, mesopleuron polished and smooth, punctate anteriorly; propodeum defined by areola and costulae with median carina basally (fig. 4); spiracle in front of middle line of propodeum; basal half of propodeum with sparse fine punctation. Wings (figs 5, 6): fore wing with radial vein r arising just after middle of pterostigma; vein r as long as vein 2-SR and not angled (fig. 5); metacarp about 6.0 times as long as distance from it to apex of marginal cell; vein 1-CU1 about 0.7 times vein 2-CU1. Wing membrane with short whitish setae. Legs: hind tibia 0.8 times as long as hind tarsus; inner hind spurs surpassing middle of basitarsus, basitarsus about 0.4 times as long as hind tarsus, fifth tarsal segment 1.2 times as long as fourth tarsal segment. Metasoma: tergites 1+2+3 (fig. 3); length of visible surface of tergite 1 about twice its apical width; length of third tergite 1.5 times second tergite; basal field of second tergite large and well separated posteriorly by a wide finely carinated furrow; dorsal surface of tergite 1 and basal field of tergite 2 with rugose punctate, tergite 3 finely punctation. Ovipositor sheath long and densely setose; setose part of ovipositor sheath 1.8 times as long as hind tibia; hypopygium long, narrow and acute apically. Colour: head and thorax black; palpi light yellow; basal third antennae yellow; remainder of antenna yellowish brown; metasoma and all legs redished yellow, but hind tibia apically, hind tarsus and ovipositor sheath dark brown; pterostigma yellowish brown with light yellow basal patch. Male: unknown. Notes: this species belongs to Apanteles ultor-group (Nixon, 1965) and can be separated from Apanteles fakhrrulhajiae Mahdihassan, 1925, from India, as follows: clearly defined areola and costulae, whole gaster redish yellow, ovipositor much longer than hind tibia; Apanteles allofulvigaster Long K, sp. n. related to Apanteles numenes Nixon, 1967, from Malaixia, but it differs from the later by having middle areola on propodeum closed towards base forming a median carina, tergite 1 not narrowed towards base, suture of tergites 2+3 wide and carinated. 2. Fornicia achterbergi Long K, sp. n. (figs 7-15) Material: Holotype, 1♀Mic.905: VN, Hatay, Thachthat (Hoalac), litchi orchards, MT 21o00’N 105o32’E, 25.V- 05.VI.2002, K. D. Long. Holotype: ♀, length of body 2.5 mm, of fore wing 2.7 mm. Head (figs 7-8): antenna shorter than body, length of third segment 1.1 and 1.3 times longer fourth and fifth segments respectively; apical segment 1.3 times longer than penultimate segment. Head in frontal view with antennal sockets far above middle level of eyes (fig. 7); width of face 1.2 times height of eye and clypeus combined; height of eyes 2.1 times width; tentorial pits small and closed to mandible base, distance between tentorial pits twice times distance from pit to eye margin. Head in dorsal view with temple roundly narrowed posteriorly (fig. 8), width of head 1.6 times its height; ocelli small and in a low triangle, the anterior tangent to the posterior ocelli cutting anterior ocellus; POL 1.25 times OOL and 2.5 times diameter of posterior ocellus. Face shiny polished with sparse punctures, vetex, occiput and temple polished smooth with sparse sharp punctures. Mesoma: mesonotum as wide as head in dorsal view; scutellum in lateral view with a strong apical spine (fig. 9); mesoscutum and scutellum with discrete punctation and dense setae; scutellum with a stronger spine apically (fig. 9); metanotum with a long spne; scutellar sulcus rather wide and deep about 0.3 times as long as scutellum and with 7 carinae (fig. 10); mesopleuron densely rugose-punctate anteriorly, smooth posteriorly; propodeum short and dull. Wings (figs 13, 14): fore wing with radial vein r arising beyond middle of pterostigma; vein r as long as vein 2-SR, and 1.25 times width of pterostigma, and comparatively gradually merging and not distinctly angled (fig. 14); metacarp about 1.2 times length of pterostigma; vein 2-CU1 1.8 and 1.5 times vein 1-CU1 and cu-a respectively. Hind wing broad, submarginal cell long, its length about 1.4 times its width. Legs: hind tibia gradually swollen apically (fig. 12) and 1.9 times as long as hind tarsus 1-5; inner hind tibial spurs 0.55 times hind basitarsus; fouth tarsal segment as long as fifth hind tarsus; inner side of hind basitarsus with special setae (fig. 12). Metasoma: tergite 1+2+3 forming carapace hiding apical segments (fig. 12); tegites 1+2+3 coarsely rugose; tergites 2+3 with wide smooth median furrows; tergite 1+2 suture smooth, tergite 2+3 suture carinate; third tergite 1.8 times longer than tergite 2. Ovipositor sheath smooth, ovipositor 0.75 times hind basitarsus (fig. 10). Colour: Head and thorax black; palpi light yellow; 2/3 basal antennae, all legs and metasoma yellow; apical third of antenna and pterostigma brown. Male: unknown. Notes: Fornicia achterbergi Long K, sp. n. is closely related to Fornicia flavoabdominis Chen & He, from China. It differs from the later by the combination of the following features: i) scutellum with a strong spine apically (fig. 9); ii): vein r almost perpendicular to pterostigma, vein r as long as 2-SR, curved and not not distinctly angled (fig. 14). Etymology: this species is named after Prof. Dr. Van Achterberg, the famous hymenopterist, who has intensively studied the Braconidae. 3. Wilkinsonellus tobiasi Long K, sp. n. (figs 16-24) Material: Holotype, 1♀Mic.697: VN, Thainguyen, §aitu, Catne, tea garden, MT 10-20/X/2006, K. D. Long; paratypes 1♂Mic. 698, 1♀Mic.699: same data as of holotype, 1♂Mic.959: Thuathien-Hue (A Luoi), MT 10-20.VIII.2005, N. Q. Truong. Holotype: ♀, length of body as long as of fore wing: 4.0 mm. Head (figs 16, 17)): antennae 1.1 times longer than body; length of scape almost 1.5 times its maximum width; third antennal segment as long as fourth and fifth segment; penultimate segment as long as apical segment, antenna acute apically. Head in frontal view with antennal sockets far above middle level of eyes; eyes large with height 2.25 times its width; face with medio-longitudinal carina below middle level of eyes (fig. 16); tentorial pits large, distance between tentorial pits 1.5 times distance from pit to eye margin. Head in dorsal view with occiput narrow and medially grooved, width of head 2.1 times its height (fig. 16); ocelli rather large, diameter of lateral ocellus (OD) about 1.3 times POL and twice OOL; face with dense rugose punctation; vertex and occiput rugose-punctate. Mesoma: Mesoscutum 0.9 times wider width of head dorsally; mesoscutum with discrete punctation anteriorly; middle lobe of mesoscutum transversely rugose-punctate; scutellar sulcus with 5 carinae (females)(fig. 21) or 6 carinae (males) ; scutellum densely punctate; mesopleuron polished with punctures and rugosities; propodeum with medio-longitudinal carina and with short transverse rugosities (fig. 21); spiracles large contiguous with oblique costulae. Wings: fore wing with radial vein r arising beyond middle of pterostigma (fig. 17); vein r 1.2 times as long as vein 2-SR and 1.2 times width of pterostigma; metacarp about 1.5 times length of pterostigma and 5.0 times as long as its distance from its to apex of marginal cell; vein 1-CU1 as long as vein cu-a and 0.4 times vein 2-CU1; vein 1-SC+M slightly curved. Hind wing rather wide; cubitellan cell about 1.7 times as long as its width. Legs: Hind coxa long, surpassing apex of third tergite, outer dorsal surface of hind coxa coarsely rugose and with a longitudinal ruga running from base to apex; outer dorsal side of hind tibia sparsely stout spinose (fig. 23); inner hind spur long, about 0.75-0.8 times as long as basitarsus; hind basitarsus about 0.9 times as long hind tarsus; fourth tarsal segment longer than fith tarsal segment (5: 4). Metasoma: Tergites 1+2+3 smooth; tergite 1 long, distinctly constricted medially and wider apically with 1 deep groove extending to apex (fig. 19); sutures between tergites faint; length of tergite 1 about 4.2 times its apical width; its apical width 1.5 times its minimum width near middle; ovipositor sheath short, hardly surpassing apex of metasoma; hypopygium protruding behind apex of metasoma. Colour.- Light yellow; scape whitish yellow with dark brown lateral sides; flagellum dark brown; fore and middle coxae white or whitish yellow; palpi and stematicum whitish yellow; pterostigma brown; lateral lobes of mesoscutum, mesosternum, apical three fourth of hind coxa, apical half of hind femur, apical third of hind tibia and hind tarsus dark brown or dark; tergites 1+2+3 whitish-yellow or white; Male: as female. Notes: Wilkinsonellus tobiasi Long K, sp. n. is closely related to Wilkinsonellus paramplus Long & Van Achterberg, 2003, from Vietnam. It differs from the later by the combination of the following features: i) the outer side of hind tibia short and stout spinose (fig. 23); ii): the scutellar sulcus with 5-6 carinae (fig. 20); iii): vein r slightly longer than vein 2-SR; iiii): tergites 1+2+3 white or whitish yellow. Etymology. This species is named after Prof. Dr. V. I. Tobias, the famous Russian hymenopterist, who was my first supervisor during my study on Braconidae.